Effect of Implementation of Chat Room-Based Blended Learning on Self-Efficacy and Student Learning Outcomes on Human Movement System Material - Muhibbudin; Khairil; Safrida; Ria Andriani; Andi Ulfa Tenri Pada (Postgraduate, University of Mataram, 2023)
Self efficacy has an important role in student achievement, high self efficacy will encourage students to excel and low self efficacy makes it difficult for students to achieve achievements in their studies. This study aims to determine the effect of implementing chat room-based blended learning on self-efficacy and student learning outcomes and the relationship between self-efficacy and learning outcomes. This study used a Quasi-Experimental method with a pretest-posttest Non-Equivalent Control Group Design. Sampling used a purposive sampling technique with a total sample of 134 students consisting of the experimental group and the control group. The instrument used to measure self-efficacy uses a questionnaire containing 45 statements, while learning outcomes are measured using 40 multiple choice questions. Data analysis used covariance analysis at a significant level of 0.05, while analysis of the relationship between self-efficacy and learning outcomes used Pearson's Product Moment correlation analysis. The results showed that there was an effect of self-efficacy and student learning outcomes (p <0.05) and there was a significant relationship between self-efficacy and student learning outcomes after implementing chat room-based blended learning. The conclusion of the study is that there is a positive influence on the implementation of chat room-based blended learning on self-efficacy and student learning outcomes in the human movement system material and there is a positive and significant relationship between self-efficacy and student learning outcomes.